The relationship between parenting stress and perceived children's social problem behavior among Chinese working mothers - Chew, Xing Jiun; Wan Jaafar, Wan Marzuki; Ghazali, Nor Mazlina (International Association of Computer Science and Information Technology (I A C S I T), 2016)
This study examines the relationship between parenting stress and perceived children's social problem behavior. The sample consists of 100 Chinese working mothers were sampled by cluster sampling methods. Parenting Stress Index-short Form and Eyberg child Behavior Inventory were employed to measure the parenting stress and children social problem behavior respectively. The result revealed that parenting stress is significantly positive correlated with perceived children social problem behavior in intensity (r = .431**, p < 0.01) and problem score (r = .716 **, p (0.0I). Besides, parental distress (r = .340**, p < 0.01), parent child dysfunction interaction (r = .398**, p < 0.01) and difficult child (r = .389**, p < 0.01) also moderately associated with perceived children social problem behavior in intensity score. The findings also noted parental distress (r = .435**, p < 0.01), parent child dysfunction interaction (r = .731**, p < 0.01) and difficult child (r = .672**, p < 0.01) also moderately associated with perceived children social problem behavior in problem score. Interestingly, the result showed household income (r = -.233**, p < 0.01) and numbers of children (r = .333 **, p < 0.01) are related to parenting stress. The result showed the higher the working hours, the lower the parenting stress (r = -.424**, p < 0.01). Hence, this study gives a guideline for the policy makers and counselors to design program which can benefit the parents and children as well.